WiXaRd: Towards a Holistic Distributed Platform for Multi-Party and Cross-Reality WebXR Experiences - Stacchio, Lorenzo; Vallasciani, Giacomo; Augello, Giulio; Carrador, Silvano; Cascarano, Pasquale; Marfia, Gustavo (2024 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2024)
Extended Reality (XR) paradigms have found applications in different areas, with vast adoption in both education and industry. Those flourished since XR enables spatial 3D object manipulation, and annotations, which have proven to be crucial for enhancing learning and task execution efficacy. In developing such experiences, inde-pendence towards the adopted device, ease of use, integration with external data sources, and real-time collaboration are pivotal factors to fit human needs. Considering these aspects, WebXR technologies could provide a solution, however, we found a lack of open-source systems that provide holistically: (i) a flexible WebXR immersive environment; (ii) a remote-streaming mechanism, to increase its accessibility; (iii) integration with the 3D external database. To this date, we here introduce WiXaRd, a WebXR and cross-reality system designed to provide such features, making it suitable for applications like collaborative remote showcasing, teaching, and training.